The Concept Of Melancholy And Typological Problem Of Transitional Era Literary Culture - Ilich Razzhivin, Anatolij; Nikolaevich Pashkurov, Aleksej; Yulievna Dulalaeva, Irina (Opción, 2019)
The article considers the issue of the worldview model of the Russian pre-Romantic elegy and its genre typology as part of the study of the general problem of the melancholic poetics in the literary culture of transitional eras. The research focuses on topical aspects of the general humanitarian theory of literary culture and typological uniqueness of literary processes of transi- tional eras considered in a general methodological aspect. The psychologi- cal and ideological areas of the phenomenon of Melancholy are analyzed from the standpoint of the men of letters closely related to the phenomenolo- gy of creative writing. A systematic review of the problem of Melancholy as a special image -archetype has been done through the dynamics of the socio-cultural situa- tion. A comprehensive analysis of the literary and religious-spiritual compo- nent of the problem is presented in the comparison of the elegies of the Russian “melancholic school” of the turn of the 18th – 19th centuries in the works of Andrey Yakubovich and Efim Smagin. The results of analytics present a summary picture of the study proposed findings and its immediate prospects. The most important of the former is a combination of a general cultural approach (context of a social and cultural situation, philosophy, aesthetic and ethical thought) with a genre-thematic aspect containing the evolution of leading ethical themes and problems, the interaction of genres within a single literary system. In the context of the lyrical poetry of the 1780s and 1810s, one of the main “driving forces” is revealed, represented by the dialogue of idyll and elegy.